Managing the product development process. Part I: an assessment. (1st January 1997) - Jenkins, S.; Forbes, S.; Durrani, T.S.; Banerjee, S.K.
Recent studies have indicated that a company's chances of success in launching new products is dependent upon the management of the new product development process. The increasing rate of technological change coupled with increasing global competition, means that a high rate of new product development and introduction in the marketplace is vital to a company's continued growth and long-term survival. In this part, methodologies for new product development, including (a) Phased Development, (b) Stage/Gate Models, (c) Product and Cycle -time Excellence - PACE and, (d) Total Design, are investigated. The strengths and weaknesses of each methodology are assessed and proposals for improved management of the new product development process in manufacturing are discussed.